1981
DOI: 10.1007/bf00441719
|View full text |Cite
|
Sign up to set email alerts
|

Aniridia, mental retardation and an unbalanced reciprocal translocation of chromosomes 8 and 11 with an interstitial deletion of 11p

Abstract: A mentally retarded female with aniridia, microcephaly and no other major malformations has been studied using G-banded prometaphase chromosomes. This study revealed a reciprocal translocation of chromosome 8 and chromosome 11 with one break point in 8q and two breakpoints in 11p. An interstitial segment of 11p is lost. Both parents have a normal karyotype. The importance of chromosome analyses of patients with aniridia and mental retardation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Two patients have been described with Wilms tumor, aniridia, genitourinary abnormalities and mental retardation (WAGR) and deletions of llp13 due to apparently unbalanced translocations of this region [ Godde-Salz and Behnke, 1981;Puissant et al, 19881. Molecular studies on the patient with the t(5;ll)(qll;pl3) by h i ssant et al [19881 demonstrated a deletion encompassing the gene for catalase (CAT).…”
Section: Addendummentioning
confidence: 99%
“…Two patients have been described with Wilms tumor, aniridia, genitourinary abnormalities and mental retardation (WAGR) and deletions of llp13 due to apparently unbalanced translocations of this region [ Godde-Salz and Behnke, 1981;Puissant et al, 19881. Molecular studies on the patient with the t(5;ll)(qll;pl3) by h i ssant et al [19881 demonstrated a deletion encompassing the gene for catalase (CAT).…”
Section: Addendummentioning
confidence: 99%
“…Aniridia is not confined to this chromosome aberration and it can also be a feature of various other aberrations including trisomy 13. Hypernephroma and gonadoblastoma manifest themselves in about a quarter to a third of patients with the syndrome and are, after the cardiac malformations, the second most frequent cause of reduced survival. 39 and familial insertional translocations are occasionally found.4'A2 A pair of monozygous twins were concordant for aniridia, but discordant for hypernephroma.43 Since the gene coding for the enzyme catalase (CAT) is also localised in 11pl3 and is deleted in almost all WAGRS patients (serum enzyme activity reduced to about 50% of normal), CAT determination can be helpful for the detection of submicroscopic deletions.…”
Section: Cytogeneticsmentioning
confidence: 99%